Dire l'indicible - Cahen, Gérald (Revue des sciences philosophiques et théologiques, 2009)
‘It is the supreme paradox of thought that it seeks to discover something which it is itself incapable of thinking’ (Kierkegaard, Philosophical Fragments). Drawing on this statement by Kierkegaard, we seek to demonstrate how every writer always seeks to approximate as nearly as possible to ‘something’ he can never entirely express, and which he only ever manages to skirt around, to evoke; and that, no doubt, because this ‘something’ does not inhabit, or no longer inhabits, the realm of words but of existence. And yet, the attempt still needs to be made to find words to express it - words to speak the unspeakable - whether through irony, poetic metaphor or in an altogether different way.